Is It Safe? : BPA and the Struggle to Define the Safety of Chemicals - Vogel, Sarah A. (Sarah Ann), 1974- (Book collections on Project MUSE., 2012)
We are all just a little bit plastic. Traces of bisphenol A or BPA, a chemical used in plastics production, are widely detected in our bodies and environment. Is this chemical, and its presence in the human body, safe? What is meant by safety? Who defines it, and according to what information? /i/Is It Safe?//i/ narrates how the meaning of the safety of industrial chemicals has been historically produced by breakthroughs in environmental health research, which in turn trigger contests among trade associations, lawyers, politicians, and citizen activists to set new regulatory standards. Drawing on archival research and extensive interviews, author Sarah Vogel explores the roots of the contemporary debate over the safety of BPA, and the concerns presented by its estrogen-like effects even at low doses. Ultimately, she contends that science alone cannot resolve the political and economic conflicts at play in the definition of safety. To strike a sustainable balance between the interests of commerce and public health requires recognition that powerful interests will always try to shape the criteria for defining safety, and that the agenda for environmental health research should be protected from capture by any single interest group.